2011
DOI: 10.1002/chem.201003147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Ring‐Opening Metathesis of Tetraalkoxy‐Substituted [2.2]Paracyclophane‐1,9‐dienes

Abstract: Tetraalkoxy-substituted [2.2]paracyclophane-1,9-dienes can be prepared in three steps from dithia[3.3]paracyclophanes. A mixture of pseudo-geminal and pseudo-ortho diastereomers is produced and the pure compounds can be separated by fractional crystallization. The solid state structures of these diastereomers reveal strongly distorted aromatic rings consistent with high levels of ring strain. Reaction of these diastereomers with the second generation Grubbs catalyst shows that only the pseudo-geminal isomer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…In an effort to combat the reported slow kinetics,19c the ROMP of pCpd was screened using various Grubbs initiators ( a – e , Scheme ). The samples were prepared with a [pCpd]/[I] ratio of 10:1, and heated to 68 °C for a period of 24–30 h. 1 H NMR spectroscopic analysis was used to monitor the polymerization, for which the unreactive pCpd regioisomer was utilized as an internal standard 19b. Polymerizations were conducted using a 93:7 ratio of the two isomers (ca.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to combat the reported slow kinetics,19c the ROMP of pCpd was screened using various Grubbs initiators ( a – e , Scheme ). The samples were prepared with a [pCpd]/[I] ratio of 10:1, and heated to 68 °C for a period of 24–30 h. 1 H NMR spectroscopic analysis was used to monitor the polymerization, for which the unreactive pCpd regioisomer was utilized as an internal standard 19b. Polymerizations were conducted using a 93:7 ratio of the two isomers (ca.…”
Section: Resultsmentioning
confidence: 99%
“…34 As previously reported for the ROMP of 4,7,12,15--tetraoctyloxy--[2.2]paracyclophane--1,9--diene and 5,8,12,15--tetraoctyloxy--[2.2]paracyclophane--1,9--diene, only the former isomer, with the long alkoxy chains in the pseudo--geminal positions, can be successfully polymerised. 35 Conversely, Zentel et al found that reducing the alkoxy chain length to a methoxy group and refluxing in toluene resulted in polymerisation of the pseudo--ortho isomer. 28 ROMP of the mixture of M2 and M3, was initiated with G3, assuming that only M2 is reactive towards metathesis.…”
Section: Poly(25--dioctyl--p--phenylenevinylene)smentioning
confidence: 99%
“…Compound 14 was isolated as a highly viscous oil in a yield of 96% after work-up, with no further purification performed. 33 The mixture of dithiacyclophanes 16 and 17 was subjected to the BSR with compound 7 and TBAF·3H 2 O (Scheme 4). The addition of Cs 2 CO 3 gave slightly improved yields, presumably due to reaction of the acidic by-products of the elimination reaction.…”
Section: Synthesis Of 47-dioctyl-[22]paracyclophane-19-dienementioning
confidence: 99%
“…A more convenient source of benzyne has been reported through the reaction of 2-(trimethylsilyl)phenyl trifluoromethanesulfonate (7) with tetra-n-butylammonium fluoride (TBAF). 33 Herein we report an improved process to prepare substituted [2.2]paracyclophane-1,9-dienes using 7 and TBAF·3H 2 O as the benzyne source and the use of this process to Benzyne precursor 7 offers major advantages over traditional sources of benzyne, but it is exceptionally expensive. 31,32 In our previous reports on the synthesis of tetraoctyloxysubstituted [2.2]paracyclophane-1,9-dienes we have used the method of Boekelheide et al, however, only low yields (<31%) were obtained.…”
Section: Introductionmentioning
confidence: 99%